Analisis determinan profitabilitas perusahaan manufaktur pada 2014-2019 - Audi Gracia Wasisto; Nora Amelda Rizal (Journal of Business & Banking, 2020)
Profitability is very important for a company to carry out their operational activities because in general they cannot not survive without the ability to generate profits. This study aims to determine the effect of working capital, firm size, company efficiency, liquidity, and leverage on profitability in manufacturing companies listed in the Indonesia Stock Exchange 2014-2019. This research used purposive sampling with 108 sample data. The data were analyzed using panel data regression using eviews 11 software. It showes that working capital, firm size, company efficiency, liquidity, and leverage simultaneously have a significant effect on profitability. Partially, working capital has a significant positive effect on profitability. Firm size has no significant positive effect on profitability (ROE), but it has a significant positive effect on profitability (EPS). Company efficiency has a significant positive effect on profitability. Liquidity has no significant positive effect on profitability (ROE) and has no negative effect on profitability (EPS). Leverage DER and LDAR have no significant negative effect on profitability. Therefore, this research can be a reference for future research to analyze the determininant of profitability.